Estrategias de desarrollo e inclusión social a través de la cultura. Las sociedades musicales de la Comunidad Valenciana y El Sistema de Abreu en Venezuela - María Luz Rivera-Fernández (Revista Iberoamericana de Estudios de Desarrollo)
Within development models, art and culture play a relevant role in social inclusion processes. The musical experience shows great potential to strengthen personal, group and community bonds. In this article I delve into the role of collective music performance and community development, from a sociological perspective of group performance practice. For this, I focus on two different realities that share the same foundation: the System of Children and Youth Orchestras and Choirs of Venezuela, founded by José Antonio Abreu in 1975, and the phenomenon of the musical societies of the Community of Valencia (Spain). In both examples, the collective practice of music generates the personal growth and social integration of those who participate in these projects. They promote integration in the group and teamwork as the basis for their pedagogical and social action. In both cases, they articulate pedagogical systems that develop the skills of the participants to be able to practice and enjoy music in a group within the community.